Agencja akredytacyjna szkolnictwa wyższego w estonii - Jan Izdebski (Krytyka Prawa, 2024)
Educational quality assurance is among the most important issues in the organisa- tion and functioning of the higher education system. The higher education system in Estonia is closely linked to the external environment. Its characteristics and the quality of education are influenced by the standards of the entire education and science system and the socio-economic environment. In Estonia, these characteris- tics are strongly influenced by the implemented innovation policy, international cooperation and computerisation in the sphere of activities of public institutions including education, education and higher education. Quality assessments of higher education are organised and carried out by the Agency for Higher Education Quality in accordance with international rules. Currently, education quality assess- ment is carried out by the Estonian Quality Agency for Education, Eesti Hariduse Kvaliteediagentuur (HAKA). Its activities are highly rated in the work of interna- tional associations for cooperation in the field of education quality assurance